Exploring the Impact of School Climate and Environmental Awareness on Cultural Competence - Sun, Jing; Ma, Wenwen; Mu, Ye; Yu, Lifang (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aims to examine the predictive power of school climate and environmental awareness on cultural competence within educational institutions. Methodology: Employing a cross-sectional design, this research engaged 320 participants from a variety of educational backgrounds through stratified sampling. Data were collected using the Multicultural Awareness, Knowledge, and Skills Survey (MAKSS) for cultural competence, the School Climate Survey (SCS), and the Environmental Awareness Scale (EAS). Linear regression analysis was conducted using SPSS version 27 to explore the relationships between school climate, environmental awareness, and cultural competence. Findings: The results reveal significant predictive relationships, with school climate (β=0.31, p